THE POTENCIES OF AUTOLOGOUS-CONDITIONED PLASMA FOR THE TREATMENT OF OSGOOD–SCHLATTER DISEASE: A LITERATURE REVIEW - SANANTA, PANJI; PUTRA, YUDHA ANANTHA KHAERUL; FUZIANINGSIH, EKA NOVIYA (Journal Medical Universitas muhammadiyah Makassar, 2025)
Osgood-Schlatter disease (OSD) is characterized by inflammation of the patellar ligament at the tibial tuberosity resulting from growth-related overuse. Traction apophysitis of the anterior component of the tibial tuberosity (ATT) happens when the quadriceps muscle contracts at the point where the proximal tibial apophysis attaches to the tibia. The recommended interventions include the administration of analgesics, the provision of instruction on physical activity, and the implementation of physiotherapy. However, the duration of signs and symptoms can be extended. Autologous-conditioned plasma (ACP) injections are increasingly being employed in treating various musculoskeletal diseases due to their elevated concentration levels of growth factors compared to whole blood. The Autologous Concentrated Platelets (ACP) solution consists solely of platelet-rich plasma (PRP) devoid of leukocytes. This concentrated PRP will be administered via injection into the affected trauma region. The present literature evaluation used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. The current literature review demonstrates that autologous conditioned plasma (ACP) is a suitable alternative therapy for osteochondritis dissecans (OSD). The efficacy of OSD treatment can be enhanced by administering autologous conditioned plasma (ACP) into the affected region. Using autologous conditioned plasma (ACP) to treat orthopaedic and traumatological conditions, such as OSD and other musculoskeletal injuries, has much potential as a therapeutic intervention in orthopaedics and traumatology.